2019
DOI: 10.1097/md.0000000000015611
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response relationship between higher serum calcium level and higher prevalence of hyperuricemia

Abstract: The aim of the study was to examine the relationship between serum calcium (Ca) levels and the prevalence of hyperuricemia (HU). The data included in this analysis were extracted from a population-based study conducted at the Xiangya Hospital Health Management Centre. Serum Ca levels were measured using the Arsenazo III method. HU was defined as the uric acid ≥416 μmol/L for male subjects, and ≥360 μmol/L for female subjects. The association between serum Ca levels and the prevalence of HU was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…In this study, we analyzed the prevalence of hyperuricemia in 1957 patients undergoing routine physical examination. The total prevalence of hyperuricemia in the healthy population was 16.6% (19.5% in males and 14.9% in females), which was similar to the prevalence of 17.5% in Changsha, Hunan Province 17 and that of 19.8% in Nanning, Guangxi Province in 2014. 18 However, this prevalence was higher than that in the Eastern Chinese population, for which the reported prevalence of hyperuricemia was 11.3% from January 2014 to December 2015, 19 and the overall prevalence of hyperuricemia of 4.2% in Jinan.…”
Section: Discussionsupporting
confidence: 64%
“…In this study, we analyzed the prevalence of hyperuricemia in 1957 patients undergoing routine physical examination. The total prevalence of hyperuricemia in the healthy population was 16.6% (19.5% in males and 14.9% in females), which was similar to the prevalence of 17.5% in Changsha, Hunan Province 17 and that of 19.8% in Nanning, Guangxi Province in 2014. 18 However, this prevalence was higher than that in the Eastern Chinese population, for which the reported prevalence of hyperuricemia was 11.3% from January 2014 to December 2015, 19 and the overall prevalence of hyperuricemia of 4.2% in Jinan.…”
Section: Discussionsupporting
confidence: 64%
“…Observational studies have suggested that total CA levels are associated with SUA in adults (12)(13)(14), lacking evidence and remaining unclear (12,13). Another cross-sectional study from Asia also showed a link between total CA levels and the prevalence of hyperuricemia in adults over 40 years (15). However, there are few studies on the relationship between total CA, SUA, and hyperuricemia in adolescents.…”
Section: Introductionmentioning
confidence: 96%
“… 41 A cross-sectional study observed a positive association between high serum calcium levels and the prevalence of hyperuricemia. 42 …”
Section: Discussionmentioning
confidence: 99%
“…41 A cross-sectional study observed a positive association between high serum calcium levels and the prevalence of hyperuricemia. 42 The high levels of serum calcium caused by excessive intestinal calcium absorption (like calcium supplementation and high dietary calcium intake), decreased renal tubular calcium reabsorption, and decreased bone mineralization reflect high concentrations of activators of calcification. High serum calcium levels can reduce calcitriol, increase serum levels of fibroblast growth factor 23, 43 and suppress vitamin D, which results in hypertension and higher levels of proinflammatory cytokines and thereby facilitating coronary atherosclerosis, carotid artery intima medial thickness, and impaired endothelial function.…”
Section: Systematic Review Of Mr Studies On Serum Calciummentioning
confidence: 99%